PERALIHAN HAK ATAS TANAH MELALUI JUAL BELI MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH (Studi Kasus Pada Kantor Pertanahan Kabupaten Sukoharjo) - MARLIANA, LENI (Dinamika Hukum, 2020)
The purpose of this study was to determine the Implementation of the Transfer of Land Rights through Sale and Purchase According to Government Regulation Number 24 of 1997 Concerning Land Registration at the Sukoharjo Land Office and to find out what obstacles occurred in the Transition of Land Rights Through Sale and Purchase at the Land Office of Sukoharjo Regency. The background of this research is the transfer of land rights through buying and selling is a legal act in the field of land that must be registered at the local Land Office to obtain legal certainty for the certificate holder, but in reality, there are still residents in Sukoharjo Regency who do not understand the importance of registering the transfer of rights on land through buying and selling and still practicing buying and selling under the hand. This research is a type of empirical/sociological juridical legal research and when viewed from the nature of the study, including descriptive research. The research location is Sukoharjo Regency Land Office. The type of data used includes primary data and secondary data. Data collection techniques used are interviews, literature studies in the form of legislation, books, journals and other documents that are relevant and related to the writing of this law. Data analysis uses qualitative data analysis. The results of this study indicate that the implementation of the transfer of land rights through sale and purchase at the Sukkoharjo Land Office is in accordance with Government Regulation Number 24 of 1997 Concerning Land Registration, namely the transfer of rights through sale and purchase can only be registrated and the name is reversed if it is completed with a deed of sale and purchase bt the PPAT. If the file is complete, the process consists of registration, payment of the transfer fee (PNBP), recording on the list of entries and submission of the certificate. Inhibiting factors in the implementation of the transfer of rights through the sale and purchase include: limited resources at the Sukoharjo Land Office so that settlement is not timely, lack of counseling for the community, the applicant’s file is incomplete, the cost of transferring rights is quite high. Keywords: Transfer of Land Rights, Sale and Purchase, Obstacles